Release coating agent, release film and application thereof

By using a release coating agent prepared by a polymer containing amino, hydroxyl and hydroxymethyl hydrophilic groups, the formed release film layer can effectively improve the castability and molding quality of the aqueous MLCC ceramic slurry, and solve the problem of poor casting of the aqueous slurry in the prior art.

CN119592206APending Publication Date: 2025-03-11ZHEJIANG JIEMEI ELECTRONICS & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411875822.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing release film for MLCC casting cannot be cast well on the aqueous MLCC ceramic slurry, mainly due to the hydrophobicity of the release layer, the ceramic slurry cannot be uniformly wet and leveled.

Method used

A release coating agent is used to combine a polymer containing amino, hydroxyl, hydroxymethyl hydrophilic groups and a cross-linking curing agent. By adjusting the molar ratio of hydrophilic groups, the surface water contact angle of the formed release film layer is between 80° and 96°, so as to balance the hydrophobicity and hydrophilicity, and improve the wettability and fluidity of the slurry.

Benefits of technology

The aqueous MLCC ceramic slurry is achieved more uniformly leveling and drying on the surface of the release film layer, reducing resistance during casting, and avoiding the problems of ceramic sheet edge retraction and uneven molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592206A_ABST
    Figure CN119592206A_ABST
Patent Text Reader

Abstract

The invention relates to the field of water-based MLCC ceramic slurry tape casting process, in particular to a release coating agent, a release film and application thereof.The release coating agent comprises a polymer with hydrophilic groups and a cross-linking curing agent, the polymer at least comprises one hydrophilic group of amino, hydroxyl and hydroxymethyl, and the cross-linking curing agent is a cross-linking curing agent. The release coating agent can be coated and cured on the surface of the base material layer to form a release layer of a release film, so that the water-based MLCC ceramic slurry can better wet the surface of the release layer, the interaction force between the slurry and the release layer is enhanced, and the interfacial property between the release layer and the slurry is optimized so as to achieve the optimal stripping performance and slurry forming quality; and the water contact angle on the surface of the release layer can be controlled to be 80-96 degrees by adjusting the molar ratio of different hydrophilic groups in the release coating agent so as to adapt to the casting process of different water-based MLCC ceramic slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of water-based MLCC ceramic slurry casting process, and in particular to a release coating, a release film and applications thereof. Background Art

[0002] Multilayer ceramic capacitors (MLCC) are widely used electronic components. They are formed by casting ceramic slurry on the surface of the release layer of the release film and solidifying it into ceramic green sheets and then stacking them. They have the characteristics of high capacity density, low resistance, excellent high-frequency performance and stability, and are widely used in mobile phones, tablets, computers, automobiles and other industries. In order to reduce production environment requirements and subsequent environmental protection treatment, more and more ceramic slurries are currently using aqueous solvents such as pure water or extremely polar solvents as the dispersion solvent of ceramic slurries. This type of ceramic slurry is also called water-based MLCC ceramic slurry.

[0003] The existing MLCC casting release film is usually made by coating a layer of silicone resin release agent on the surface of the PET base film, and cross-linking and curing it under a platinum catalyst at 130-150°C to form a release layer, thereby making a release film. For example, the patent with publication number CN115746364B discloses a release film used for MLCC casting, including a polymer film and a release coating liquid coated on the polymer film; the polymer film layer is a high-performance BOPET film, and the thickness of the BOPET film is 15 to 300 μm; the release coating liquid includes, by mass fraction: a main agent of 8 to 33%, a curing agent of 0.35 to 5%, a catalyst of 0.25 to 5.5%, an inhibitor of 0.06 to 0.85%, a composite solvent of 35 to 87.5%, an antistatic agent of 0.08 to 0.8%, a defoaming agent of 0.03 to 0.55%, and an anchoring agent of 0.06 to 0.6%; the main agent is an alkenyl-terminated siloxane, and the curing agent is an imide ring-modified active hydrogen-containing polysiloxane.

[0004] The release layer of the above release film uses alkenyl-terminated siloxane as the main agent and imide ring-modified active hydrogen-containing polysiloxane as the curing agent, and both are hydrophobic, resulting in the inability of water-based MLCC ceramic slurry to be well cast on the surface of the release film. Summary of the invention

[0005] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a release coating agent that can be used in conjunction with water-based MLCC ceramic slurry casting, a release film prepared by using the release coating agent and its application.

[0006] A first aspect of the present invention provides a release coating, characterized in that the release coating comprises a polymer having a hydrophilic group and a cross-linking curing agent, and the polymer comprises at least one hydrophilic group selected from the group consisting of an amino group, a hydroxyl group, and a hydroxymethyl group.

[0007] The polymer used in the present invention contains at least one hydrophilic group selected from the group consisting of amino, hydroxyl and hydroxymethyl, i.e., the molar ratio of amino, hydroxyl and hydroxymethyl is 0-1:0-1:0-1. When the layer formed by coating and curing of the release coating is used for casting water-based MLCC ceramic slurry, the hydrophilic group can form hydrogen bonds with water molecules or polar groups in the aqueous solvent in the water-based MLCC ceramic slurry, thereby increasing the interaction force between the layer surface and the water-based MLCC ceramic slurry, reducing the free energy at the interface, improving the wettability and fluidity of the slurry on the layer surface, reducing the resistance during the casting process, and allowing the slurry to flow more evenly on the layer surface and dry to form a flat ceramic green sheet without shrinkage of the edge of the ceramic slurry, which would result in the ceramic green sheet being unable to be cast or having poor flatness after casting.

[0008] In some embodiments, the water contact angle of the surface of the layer formed by coating and curing the release coating agent is 80° to 96°.

[0009] Since the oxygen atom in the hydroxyl group has a strong electronegativity and can form hydrogen bonds with water molecules, it exhibits strong hydrophilicity. Although the nitrogen atom in the amino group can also form hydrogen bonds with water molecules, its electronegativity is weaker and its hydrophilicity is not as good as that of the hydroxyl group. The hydrophilicity of the hydroxymethyl group is between that of the amino group and the hydroxyl group, because it contains a hydroxyl group, but the connection between the hydroxyl group and the methyl group will slightly reduce its hydrophilicity. When the hydrophilic groups of the polymer are all hydroxyl groups, the water contact angle of the layer surface formed after the release coating is coated and cured is 80°; when the hydrophilic groups of the polymer are all amino groups, the water contact angle of the layer surface formed after the release coating is coated and cured is 96°; when the hydrophilic groups of the polymer are all hydroxymethyl groups, the water contact angle of the layer surface formed after the release coating is coated and cured is 91°. Therefore, the present invention can adjust the water contact angle of the layer surface formed by coating and curing the release coating to 80°~96° by adjusting the molar ratio of amino, hydroxyl and hydroxymethyl, balance the hydrophobicity and hydrophilicity of the layer, so that different aqueous MLCC ceramic slurries can wet the layer surface well, enhance the interaction force between the slurry and the layer, facilitate the uniform casting of the slurry and the subsequent drying and curing process, and optimize the interface properties between the layer and the slurry to achieve the best stripping performance and slurry molding quality.

[0010] In some embodiments of the present invention, the polymer comprises a melamine resin comprising the following structural units:

[0011]

[0012] X is selected from a hydrogen atom, a hydroxyl group, and a hydroxymethyl group.

[0013] In the embodiment, when X is 2 hydrogen atoms, the melamine resin is a melamine resin A containing amino groups;

[0014] When X is a hydroxyl group, the melamine resin is a melamine resin B containing a hydroxyl group;

[0015] When X is a methylol group, the melamine resin is a melamine resin C containing a methylol group.

[0016] The melamine resin is one or more of a melamine resin A containing an amino group, a melamine resin B containing a hydroxyl group, and a melamine resin C containing a methylol group.

[0017] In the embodiment, by setting the polymer to melamine resins A, B, and C and controlling the addition amount of melamine resins A, B, and C, thereby controlling the molar ratio of the amino group, hydroxyl group, and methylol group, the peeling force of the layer surface formed after the release coating is coated and cured relative to the Nitto 31B tape can be adjusted to 20 to 600 g.

[0018] In some embodiments of the present invention, the polymer comprises an acrylic resin comprising the following structural units:

[0019]

[0020] R 1 is a hydrogen atom or a methyl group, R 2 One selected from amino, hydroxyl and hydroxymethyl.

[0021] In the embodiment, when R 2 When it is an amino group, the acrylic resin is an acrylic resin A1 containing an amino group;

[0022] When R 2 When it is a hydroxyl group, the acrylic resin is an acrylic resin B1 containing a hydroxyl group;

[0023] When R 2 When it is hydroxymethyl, the acrylic resin is acrylic resin C1 containing hydroxymethyl.

[0024] The acrylic resin is one or more of an acrylic resin A1 containing an amino group, an acrylic resin B1 containing a hydroxyl group, and an acrylic resin C1 containing a hydroxymethyl group.

[0025] In the embodiment, by setting the polymer to acrylic resins A1, B1, C1 and controlling the addition amount of acrylic resins A1, B1, C1, thereby controlling the molar ratio of the amino group, hydroxyl group and methylol group, the peeling force of the layer surface formed after the release coating is coated and cured relative to the Nitto 31B tape can be adjusted to 600-1100g.

[0026] In some embodiments of the present invention, the release coating comprises 1 to 8 weight % of a polymer, 0.01 to 0.5 weight % of a cross-linking curing agent, and 91.5 to 98.96 weight % of a solvent.

[0027] In some embodiments of the present invention, the solvent is selected from one of toluene, butyl acetate, butanone, and ethyl acetate.

[0028] In the embodiment, the polymer containing a hydrophilic group is one of the main performance components of the release coating, which provides the basic structure and performance of the layer formed by the release coating and curing. The performance of the layer formed by the release coating and curing is ensured by precisely controlling the content of the polymer. The cross-linking curing agent will react with the polymer at high temperature to promote the cross-linking and curing of the polymer, thereby improving the mechanical properties and stability of the layer. When the weight ratio of the cross-linking curing agent is too small or too much, it is easy to cause incomplete cross-linking polymerization of the polymer, causing unstable peeling force, layer delamination, low residual bonding rate and other undesirable phenomena. In the embodiment, a solvent is used to dissolve the polymer and the cross-linking curing agent to facilitate coating and form a uniform coating. After the release coating is coated, dried and cured, a cross-linked structure can be formed to improve the mechanical properties and heat resistance of the layer, and avoid the problems of layer delamination and low residual bonding rate.

[0029] In some embodiments of the present invention, the cross-linking curing agent is a weakly acidic substance containing a methyl functional group. In the embodiment, the weakly acidic substance containing a methyl functional group as a cross-linking curing agent can undergo a dehydrogenation cross-linking reaction with some hydrophilic groups of the polymer under high temperature conditions (120-140°C) to form a three-dimensional network structure, thereby enhancing the performance of the layer formed by the release coating and curing, and the remaining hydrophilic groups serve as functional groups to balance the hydrophobicity and hydrophilicity of the surface of the layer formed by the release coating and curing.

[0030] In some embodiments of the present invention, the cross-linking curing agent is selected from one of methanesulfonic acid, benzenesulfonic acid or hexylsulfonic acid. Since the number of hydrophilic groups is consumed during the dehydrogenation cross-linking reaction between the cross-linking curing agent and some hydrophilic groups in the polymer, the hydrophilicity of the layer formed by coating and curing is reduced, so a cross-linking curing agent containing strong hydrophilic groups such as sulfonic acid groups is used, and sulfonic acid groups are introduced during the cross-linking and curing process. The sulfonic acid groups can react chemically with groups such as hydroxyl (-OH), methylol (-OCH3) or amino (-NH2) in the polymer, so that a cross-linked structure is formed between the molecules of the polymer, and the hydrophilicity of the surface of the layer formed by the coating and curing of the release coating is balanced while forming a three-dimensional network structure. During the cross-linking and curing process, the interfacial adhesion between the layer formed by the coating and curing of the release coating and the coated substrate layer is enhanced, because the cross-linking reaction strengthens the intermolecular force between the layer formed by the coating and curing and the substrate layer, thereby improving the adhesion of the layer formed by the coating and curing to the substrate layer.

[0031] When the water-based MLCC ceramic green sheet needs to be peeled off from the layer formed by coating and curing the release coating, the cross-linked and cured layer has a smooth surface, so that the ceramic green sheet has a stable peeling force when peeling, and the layer will not adhere to the ceramic green sheet.

[0032] A second aspect of the present invention provides a release film, comprising a substrate layer and a release layer, wherein the release layer is formed by coating the release coating according to any one of the first aspects on one or both sides of the substrate layer and cross-linking and curing the surface.

[0033] In some embodiments of the present invention, the thickness of the release layer is 100-300 nm.

[0034] In some embodiments of the present invention, the surface water contact angle of the release layer side of the release film is 80° to 96°.

[0035] In the embodiment, the peeling force of the release layer is adjusted by adjusting the thickness of the release layer. The greater the thickness, the smaller the peeling force.

[0036] In the embodiment, since the oxygen atom in the hydroxyl group has a strong electronegativity and can form hydrogen bonds with water molecules, it exhibits a strong hydrophilicity. Although the nitrogen atom in the amino group can also form hydrogen bonds with water molecules, its electronegativity is weaker and its hydrophilicity is not as good as that of the hydroxyl group. Therefore, the hydrophilicity of the hydroxyl group is greater than that of the hydroxymethyl group, which is greater than that of the amino group.

[0037] When all the hydrophilic groups of the polymer are hydroxyl groups, the surface water contact angle of the release coating after drying and curing is 80°. When all the hydrophilic groups of the polymer are amino groups, the surface water contact angle of the release coating after drying and curing is 96°. By adjusting the ratio of the above three hydrophilic groups, the surface water contact angle of the release layer can be set to 80°~96°, so that the release layer formed after the release coating is coated and cured has excellent leveling properties and is suitable for different water-based MLCC ceramic slurry castings, so that the water-based MLCC ceramic slurry will not fall off during the storage process after being cast into ceramic green sheets, and can be easily peeled off when the ceramic green sheets are peeled off, and the release layer of the release film will not remain on the surface of the ceramic green sheets after peeling.

[0038] In some embodiments of the present invention, the substrate layer is a transparent film made of polyethylene terephthalate, and the average roughness R of the substrate layer is a ≤0.5um, ten-point average height R of the microscopic roughness of the substrate layer z ≦0.7um, maximum height difference R of substrate layer max ≦1.5um. In the embodiment, by limiting the surface parameters of the substrate layer, the smoothness and consistency of the substrate layer surface are controlled to ensure the adhesion effect of the release layer and the surface performance of the final formed release film.

[0039] In some embodiments of the present invention, the release layer is prepared by coating the release coating on the surface of the substrate layer and then drying and curing the coating under a tension of 80 to 250 N / m, a temperature of 120 to 180° C., and a time of 10 to 40 seconds.

[0040] Drying under the above conditions can not only ensure that the release coating can be completely cross-linked and cured to achieve stable peeling properties, but also ensure that the substrate layer will not deform and affect the flatness of the release film.

[0041] The third aspect of the present invention provides an application of the release film as described in the second aspect, characterized in that the release film is used in a water-based MLCC ceramic slurry casting process.

[0042] The water-based MLCC ceramic slurry refers to a ceramic slurry that uses pure water or a highly polar aqueous solvent as a dispersing solvent.

[0043] By implementing the above technical solution, the present invention has the following beneficial effects:

[0044] The polymer used in the release coating of the present invention contains a hydrophilic group selected from amino, hydroxyl and hydroxymethyl, which can be coated and cured on the surface of the substrate layer to form a release layer of the release film. When the release layer of the above-mentioned release film is used for casting water-based MLCC ceramic slurry, the hydrophilic group can form hydrogen bonds with water molecules or polar groups in the aqueous solvent in the water-based MLCC ceramic slurry, thereby increasing the interaction force between the surface of the release layer and the water-based MLCC ceramic slurry, which is beneficial to the uniform casting of the slurry and the subsequent drying and curing process, and optimizes the interface properties between the release layer and the slurry to achieve the best stripping performance and slurry molding quality, and controls the water contact angle of the release layer surface to 80°~96° by adjusting the molar ratio of different hydrophilic groups in the release coating to adapt to different water-based MLCC ceramic slurry casting processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of measuring the angle θ in the performance test. DETAILED DESCRIPTION

[0046] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments.

[0047] Embodiment 1:

[0048] This embodiment provides a release coating, and the preparation steps specifically include:

[0049] Different masses and types of polymers and cross-linking curing agents were dissolved in 100 g of toluene to obtain several groups of release coating samples. The specific masses and proportions of the components are shown in Table 1:

[0050] Table 1 Components

[0051]

[0052] The release coating samples 1 to 10 prepared above were coated on one side of the substrate layer, and dried and cross-linked and cured under the conditions of a tension of 150 N / m, a temperature of 150° C., and a time of 30 s to prepare several groups of release film samples 1 to 10. The substrate layer was a transparent film made of polyethylene terephthalate, and the average roughness of the substrate layer was R a ≤0.5um, ten-point average height R of the microscopic roughness of the substrate layer z ≦0.7um, maximum height difference R of substrate layer max ≦1.5um.

[0053] Comparative Example 1:

[0054] In this comparative example, a release film was prepared according to the raw materials and steps of Example 1 of patent CN 115746364 B to obtain a release film sample 11.

[0055] Performance Testing

[0056] The surface water contact angle, peeling force and residual adhesion rate of each group of release films prepared in Example 1 and Comparative Example 1 were measured, and the test method was as follows:

[0057] Surface water contact angle test method:

[0058] Using the drop angle measurement method, a pure water droplet is projected on the release layer surface of the release film, or a water droplet is projected on the release layer surface of the release film immersed in pure water, and then the angle θ between the tangent line and the interface is directly measured. The measurement diagram of the angle θ is shown in the figure. Figure 1 As shown, the size of the water drop angle is directly measured, which is the surface water contact angle of the release film.

[0059] Peel force test method (relative to NITTO 31B tape):

[0060] 1) Take a 25 mm wide and about 200 mm long tape (NITTO 31B tape) and stick it on the test surface (release surface) of the film, and roll it repeatedly twice with an automatic roller.

[0061] 2) After applying the tape, let it stand for 20 minutes, and the temperature and humidity are controlled at (temperature 20-26°C, humidity 20-60%).

[0062] 3) Use double-sided tape to stick to the non-test surface of the sample and fix it on the standard steel plate for testing.

[0063] 4) Install the material on the fixture and test it with a tensile testing machine by stretching the test tape at 180°. The data displayed on the tensile testing machine computer is the peel force (g / in) of the test piece. The average of the five values ​​is the test result.

[0064] Residual adhesion test method (relative to NITTO 31B tape):

[0065] 1) Place the test steel plate on an automatic roller press, remove the tape pasted with the release film from the tensile machine, roll it back and forth twice with the automatic roller press, and stick the test tape on a standard stainless steel plate to obtain "sample A".

[0066] 2) Place a standard stainless steel plate on an automatic roller press, and use the automatic roller press to roll the blank test tape (the same batch of tapes as used in the peel strength test) back and forth twice on the standard stainless steel plate to obtain "Sample B".

[0067] 3) After "Sample A" and "Sample B" have been left to stand for 5 minutes, reset the tensile machine and install the bonded samples on the tensile machine fixture (the lower fixture clamps the lower part of the steel plate, and the upper fixture clamps the tail end of the tape).

[0068] 4) Click the "Test" button to test the release force (the tensile machine stretches in a 180° tensile direction and the peeling speed is 300mm / min). The average peeling load displayed on the computer is the average peeling force of the test sample.

[0069] 5) The average peel force value read out of the "Sample A" test is recorded as "A", and the average peel force value read out of the "Sample B" test is recorded as "B".

[0070] 6) Calculated by the formula: Residual bonding rate = A / B*100%.

[0071] Water-based MLCC ceramic slurry castability:

[0072] Place an aqueous MLCC ceramic slurry whose solvent is a mixture of deionized water and ethanol (volume ratio of 1:1) on the release layer surface of the above-mentioned release film, and use a scraper to level the slurry. If the slurry boundary does not shrink after leveling, it is OK. If it shrinks and the leveling is poor, it is NG.

[0073] The test results are shown in Table 2.

[0074] Table 2 Performance test results

[0075] sample Surface water contact angle (°) Peel force(g) Residual bonding rate (%) Castability 1 96 20 88 OK 2 80 600 97 OK 3 91 300 96 OK 4 93 150 93 OK 5 95 70 90 OK 6 82 500 95 OK 7 91 250 89 OK 8 96 700 86 OK 9 80 1000 95 OK 10 92 800 91 OK 11 120 10 88 NG

[0076] According to samples 1 to 10, the present invention controls the surface water contact angle of the release film by controlling the molar ratio of hydrophilic groups such as amino, hydroxyl, and hydroxymethyl contained in the polymer in the release coating. The surface water contact angle can be controlled within the range of 80° to 96°, thereby achieving excellent castability of water-based MLCC ceramic slurry.

[0077] At the same time, since melamine resin usually has higher hardness and wear resistance, the prepared release film has a higher cross-linking density and the formed film layer is harder, while acrylic resin usually has better flexibility, the prepared release film has a lower cross-linking density and the formed film layer is softer. Therefore, the peeling force of the release film can be controlled by controlling the type and addition amount of the polymer in the release coating.

[0078] However, since the polymer used in sample 11 prepared in comparative example 1 does not contain a hydrophilic group, the water contact angle of the release layer side surface of the prepared release film is large and the surface is hydrophobic, which is not suitable for the casting of water-based MLCC ceramic slurry.

[0079] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A release coating, characterized in that: The release coating comprises a polymer having a hydrophilic group and a cross-linking curing agent, wherein the polymer comprises at least one hydrophilic group selected from the group consisting of an amino group, a hydroxyl group and a hydroxymethyl group.

2. The release coating according to claim 1, characterized in that: The water contact angle of the surface of the layer formed by coating and curing of the release coating agent is 80° to 96°.

3. The release coating according to claim 1, characterized in that: The polymer comprises a melamine resin, and the melamine resin contains the following structural units: X is selected from a hydrogen atom, a hydroxyl group, and a hydroxymethyl group.

4. The release coating according to claim 1, characterized in that: The polymer includes an acrylic resin, and the acrylic resin contains the following structural units: R 1 is a hydrogen atom or a methyl group, R 2 One selected from amino, hydroxyl and hydroxymethyl.

5. The release coating according to claim 3 or 4, characterized in that: The release coating comprises 1 to 8 weight percent of a polymer, 0.01 to 0.5 weight percent of a cross-linking curing agent and 91.5 to 98.96 weight percent of a solvent.

6. The release coating according to claim 5, characterized in that: The cross-linking curing agent is a weakly acidic substance containing a methyl functional group.

7. The release coating according to claim 6, characterized in that: The cross-linking curing agent is selected from one of methanesulfonic acid, benzenesulfonic acid or hexanesulfonic acid.

8. A release film, comprising a substrate layer and a release layer, characterized in that: The release layer is formed by coating the release coating agent according to any one of claims 1 to 4 or 6 to 7 on one or both sides of the substrate layer and cross-linking and curing the surface.

9. The release film according to claim 8, characterized in that: The surface water contact angle of the release layer side of the release film is 80° to 96°.

10. A use of the release film according to claim 9, characterized in that: The release film is used in a water-based MLCC ceramic slurry casting process.

Citation Information

Patent Citations

  • A release film for MLCC casting and its preparation method

    CN115746364B

  • Release film

    JP2021091127A

  • Coating composition for release film, coating for release film, release film and article having release film

    JP2022013207A

  • Laminated film

    US20210277197A1

  • Hydrophilic compositions which are fog-resistant

    US5262475A